A first report of separation calls in southern yellow-cheeked gibbons (Nomascus gabriellae) in captivity - Hradec, Michal; Illmann, Gudrun; Bolechová, Petra (Primates; journal of primatology, 2021)
The effects of social separation, including vocalization, have been studied for a very long time in non-human primates under laboratory conditions. As part of the long-term research on the vocal behaviour of Nomascus gibbons in zoos, this study provides the first record of calls of the southern yellow-cheeked gibbon (Nomascus gabriellae) in response to involuntary separation. Our study revealed that calls were also emitted by an infant (aged 1 year 8 months), and that the acoustic structure of the infant's calls was similar to that of older individuals' calls. Separation-induced calls seem to have a shorter developmental convergence than vocalizations with a stable pattern (which are specific for species and sex). The acoustic structure of the calls reported here comprised simple syllables, and differed from the sex- and species-specific vocal patterns of this species. Our findings demonstrate a novel paradigm in this genus, and provide evidence of the ability of gibbons to express distress when socially separated.
Keywords: Animals; Female; Hylobatidae; Age Factors; Vocalization; ženské pohlaví; věkové faktory; Nomascus; Separation call; Male; Vocalization, Animal; zvířata v ZOO; Social Behavior; zvířata; mužské pohlaví; Animals, Zoo; sociální chování; vokalizace zvířat; Gibbons